From Jurisprudence to Social Responsibility: “The Rule of Benevolence as a Vital Need" (Journal of Imam Al-Kadhim College, 2024)
Abstract:The rule of benevolence is so important that it is necessary to stop at it and search into the depths of its evidence and the dimensions that it extends to. It is one of the jurisprudential rules that extend socially, as it is present in many situations in which benevolence is provided for the motive of benevolence to others, and this may be accompanied by something that calls for guarantee, so comes the role of The jurisprudential rule is to deny his guarantee for the reason of goodness and benevolence that moved him and called him to that position Since the goal behind this rule is not to include the benefactor in it, and it represents the solution to many issues and situations that occur in society, it is a jurisprudential rule and a societal need. The research came after the introduction with six sections, the first section of which was concerned with introducing the rule of benevolence linguistically and terminologically, the second section was devoted to explaining its importance jurisprudentially and socially, and the third section was concerned with explaining the evidence for this rule, which is the Qur’anic and narrative evidence indicating this rule, then the evidence of consensus and the building of rational people, and was devoted to The fourth section clarifies the limits of the rule, while the fifth section reviews the problems arising from the rule of charity and their response, and the sixth and final section is devoted to presenting applied models.